2006
DOI: 10.1016/j.atmosenv.2005.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Process studies of odour emissions from effluent ponds using machine-based odour measurement

Abstract: Odours caused by intensive piggery operations have become a major environmental issue in the piggery industry in Australia. Effluent ponds are the major source of odours in typical piggeries. It is assumed that the odour emissions from ponds are mainly driven by pond loading rate. However, there are few data to corroborate this concept.Allied to this is the need for a convenient and low cost method of odour measurement, which can be used as an alternative method for current olfactometry. The present odour meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Esta técnica, apesar de ser padronizada dentro das indústrias, apresenta um elevado custo e subjetividade exacerbada. Deste modo, o NE propõe ser um grande avanço tecnológico na análise de odores (12).…”
Section: Fundamentos Do Nariz Eletrônicounclassified
“…Esta técnica, apesar de ser padronizada dentro das indústrias, apresenta um elevado custo e subjetividade exacerbada. Deste modo, o NE propõe ser um grande avanço tecnológico na análise de odores (12).…”
Section: Fundamentos Do Nariz Eletrônicounclassified
“…Another study aiming to characterize and monitor the quality of polluted waters was conducted by Sohn et al [ 116 ]. The work had the aim to use electronic noses for the characterization of pollutant waters in terms of volatile solids load, by correlating said parameter with the odor concentration of the air over the polluted water (headspace).…”
Section: Electronic Nose Applications In Environmental Monitoringmentioning
confidence: 99%
“…The electronic nose they used for the study turned out to be able to detect variations in the air odor concentration, and is therefore considered suitable as detector of possible anomalies downstream of odor abatement systems in wastewater treatment plants. A first study on a real abatement system was reported by Sohn et al [ 116 ]. More in detail, the authors investigated the possibility to monitor a biofiltrating system for the treatment of odorous air from a pig livestock, using a commercial electronic nose, Aroma Scan A32S, equipped with 32 CP sensors.…”
Section: Electronic Nose Applications In Environmental Monitoringmentioning
confidence: 99%
“…Sohn et al used an artificial neural network, trained by the data sets obtained with an electronic nose and dynamic dilution olfactometry, to predict the pig farm odour concentrations emanating from an effluent pond and to develop a confident, rapid, and cost-effective technique for odour measurement [ 168 ]; in addition they demonstrated the relationship between odour emission rates and pond loading rates on pig farm effluent ponds and the increased magnitude of emissions from a heavily loaded effluent pond [ 169 ].…”
Section: Olfactometry and E-noses: Comparison And Integrated Approachmentioning
confidence: 99%